Side chain liquid crystalline polyacetylene derivatives - synthesis and properties - Akagi, K.; Goto, H.; Murakami, J.; Silong, S.; Shirakawa, H. (The Society of Photopolymer Science and Technology, 1999)
Liquid crystalline (LC) polyacetylene derivative with a hexamethylene chain as a spacer in LC side chain was synthesized. The acetylene monomer substituted with LC group showed both nematic and smectic phases in the cooling process. The polymerizations of the monomers were carried out using Ziegler-Natta and metathesis catalysts. The polymers thus prepared showed smectic phases in healing and cooling processes, indicating an enantiotropic nature. We found that the mesophase of the present polymer is more stabilized with a longer methylene spacer.